Mechanical Modeling of Human Platelets Membrane - Sayeur, Mathieu (Université d'Ottawa / University of Ottawa, 2015)
In an effort to help understand the mechanical properties of human platelets, their deformations were measured using micropipette experiments over an aspiration pressure range of 1-5 cmH2O, in steps of 1 cmH2O. The experiments confirmed the previously reported linear relationship between deformation and pressure. The experimental results were used to determine the material constants of a thin-axisymmetric shell model based on a strain-energy constitutive relation to describe the platelet deformations under aspiration. The model was successful in capturing the experimental deformations. It also suggested that the mechanical properties of human platelets are not significantly influenced by their volumes, but do vary depending on the platelets’ undeformed shape ratios. In addition, the model suggested that platelet membrane ruptures due to micropipette aspiration may be strain-related. The limitations of the experimental methods arising from direct contact with reactive cells such as platelets are highlighted, prompting the need for developing new methods which will not require the use of inhibition agents that alter the platelets’ mechanical properties. Afin d’approfondir les connaissances des propriétés mécaniques des plaquettes humaines, leurs déformations ont été mesurées lors d’expériences avec des micropipettes pour des pressions d’aspiration de 1-5 cmH2O, par intervalles de 1 cmH2O. Les expériences ont confirmé la relation linéaire entre les déformations et la pression d’aspiration telle que précédemment publié. Les données expérimentales ont été utilisées pour déterminer les constantes matérielles d’un modèle de membrane mince axisymétrique basé sur une loi de comportement caractérisant l’énergie de déformation. Le modèle simule bien les déformations des plaquettes sous aspiration; il suggère également que les propriétés mécaniques des plaquettes humaines ne sont pas influencées significativement leur volume, mais varient en fonction de leurs formes avant déformation. De plus, le modèle suggère que les ruptures de la membrane des plaquettes sous aspiration seraient reliées aux déformations. Les limites des méthodes expérimentales utilisées, du fait du contact direct avec des cellules aussi réactives que les plaquettes sont soulignées, et mettent l’emphase sur le besoin de mettre au point de nouvelles méthodes ne requérant pas d’agents d’inhibitions qui altèrent les propriétés mécaniques des plaquettes.
Keywords: Platelets; Mechanics; Constitutive Model; Micropipette Aspiration; Energy Strain Relationship; Mechanical Properties